Transmobilities: mobility, harassment, and violence experienced by transgender and gender nonconforming public transit riders in Portland, Oregon. Issue 10 (3rd October 2017) - Lubitow, Amy; Carathers, JaDee; Kelly, Maura; Abelson, Miriam
Abstract: This research endeavours to fill a conceptual gap in the social science literature on gender, public space, and urban mobilities by exploring how transgender and gender nonconforming individuals experience public transit. Although previous research has surveyed gender minorities about harassment and discrimination in a range of environments, little is known about the quality or content of these experiences. Drawing from 25 interviews with transgender and gender nonconforming individuals in Portland, Oregon, this article finds that gender minorities experience frequent harassment while engaging with the public transit system. We articulate the concept of transmobilites to describe the ways that transgender and gender nonconforming individuals experience a form of mobility that is altered, shaped, and informed by a broader cultural system that normalizes violence and harassment towards gender minorities. We conclude that gender minorities have unequal access to safe and accessible public transportation when harassment is widespread, normalized, and when policies prohibiting discrimination remain unenforced on urban public transit.